2013
DOI: 10.1002/dneu.22096
|View full text |Cite
|
Sign up to set email alerts
|

Increasing our understanding of human cognition through the study of fragile X syndrome

Abstract: Fragile X Syndrome (FXS) is considered the most common form of inherited intellectual disability. It is caused by reductions in the expression level or function of a single protein, the Fragile X Mental Retardation Protein (FMRP), a translational regulator which binds to approximately 4% of brain messenger RNAs. Accumulating evidence suggests that FXS is a complex disorder of cognition, involving interactions between genetic and environmental influences, leading to difficulties in acquiring key life skills inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 391 publications
(573 reference statements)
0
12
0
Order By: Relevance
“…FMRP has been implicated in translational control, associating with actively translating polyribosomes in ribonucleoprotein particles (reviewed in Ref. 39). ERH is a highly conserved protein that has been implicated in nuclear gene expression (40,41) and cell growth (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…FMRP has been implicated in translational control, associating with actively translating polyribosomes in ribonucleoprotein particles (reviewed in Ref. 39). ERH is a highly conserved protein that has been implicated in nuclear gene expression (40,41) and cell growth (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…All three proteins associate with polyribosomes and messenger ribonucleoprotein particles (mRNPs), are found at spines, and are expressed in similar patterns in the brain, presenting the question of whether they perform redundant functions (Cook et al, 2014; Tamanini et al, 1997, 2000). However, until now, nothing was known about the mRNA targets of FXR1P or its role in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that TOP3B actually participates in mRNA metabolism as well as DNA processing because TOP3B was found to be associated with the fragile X mental retardation protein (FMRP), an mRNA-binding protein that interacts with polyribosomes and regulates translation. The FMRP is encoded by the FMR1 gene, mutations in which cause fragile X syndrome (OMIM #300624), a genetic condition that involves developmental delays, learning disabilities, autism, attention deficit disorder, and characteristic physical features such as large ears, craniofacial features, macroorchidism, and hyperflexible fingers [Cook et al, 2014]. The detailed studies of Stoll et al [2013] found that TOP3B plays a role in the metabolism of FMRP-bound mRNAs.…”
Section: Resultsmentioning
confidence: 99%